In Krise und Kränkung mit Hoffnung gekrönt: Reflexionen zu einem Pandemiejahr aus kirchenpraktischer Perspektive - Bammel, Christina-Maria (Evangelische Theologie, 2021)
A year of church under pandemic conditions: Taking Christmas as the starting point of God's self-revelation and spiritual reassurance in this shaky and unsettled pandemic world Provost Dr. Christina-Maria Bammel presents in a personal essay her view of the theological, practical, spiritual church-leadership challenges of this time. On the one hand she looks back and attempts to clarify how the church, in its various manifestations, in congregation and regional church, in physical and virtual presence, has acted so far. On the other hand, she looks ahead and proposes how best to respond to current concerns, to long-known phenomena and new processes, i.e. reorganizing parishes for the good of the neighborhood, which have gained relevance and urgency. There is no simple way to speak of a life after Covid 19, but there is a spiritual and material need to accept that from now on, we have to face a future church life with the virus.